Preparation and diagnosis of new types of Schiff bases one-and two- claw and complexes to study the effectiveness of chemical - Baghdad Science Journal (مجلة بغداد للعلوم)
In this research we prepared shiff bases unilateral claw( benzyl imine aniline ) and Bilateral claw ( benzayal-2-imine phenol ) in high purity reach to 98% , which it's prepared from aromatic amine with aldehydes, it's solid,thermosetting, not dissolved in water in general. Diagnosed prepared article by using infra red spectroscopy (IR) which shows azomethen grop at 1640cm-1 At this diagnosis we suggest tetra headral mechanism in this Circumstances For a reaction.